The Politics of Accommodation: German Social Democracy and the Catholic Church - Dowell, Jack D. (A journal of church and state, 1965)
Jack D. Dowell; The Politics of Accommodation: German Social Democracy and the Catholic Church, Journal of Church and State, Volume 7, Issue 1, 1 January 1965,